The Potential of Hanjuang Merah (Cordyline fruticose) Antibacterial Liquid Body Wash - Rahayu, Emy; Rahmanina, Lilih; Pasaribu, Tupaida; Maulida, Maulida; Dewi, Mirnawati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The skin is the outermost layer of tissue that has the function of covering and protecting the surface of the human body. Unhygienic skin will trigger skin infections caused by various microorganisms. One of them is bacteria. Hanjuang merah (Cordyline fruticosa) is a type of plant that is often used as a traditional medicine, especially for the Dayak community. However, research on the use of the Cordyline fruticosa plant in producing liquid body wash formulations that are efficacious as antibacterial against Staphylococcus aureus has not been carried out so far. The purpose of this study is to identify the potential of Cordyline fruticosa as a formulation of liquid body wash formulations and to find the effectiveness of Cordyline fruticosa in inhibiting infections caused by S. aureus bacteria made in the form of liquid body wash. The method used in the extraction is maceration and the manufacture of liquid body wash according to the formulation that has been made, while the disc diffusion method with concentrations of 5% (F1), 10% (F2), and 15% (F3) is used in antibacterial tests. Liquid body wash preparations with the largest inhibitory zone level at a concentration of 15% (F3). The concentration of 15% (F3) is effective in inhibiting the growth of S. aureus bacteria which is characterized by the formation of an inhibition zone around the disk.